Trends in cardiovascular disease incidence and mortality in Beijing, 2012–2022 - Aijuan Ma; Zhiqing Zeng; Xiao Li; Chen Yang; Jiayu Wang; Gang Li; Moning Guo; Feng Lu; Li Nie; Chen Xie; Bo Jiang; Jun Lv; et al. (BMC Public Health, 2026)
Abstract Objective To assess the trends in cardiovascular disease (CVD) incidence and mortality among Beijing adults, providing a scientific basis for the development of chronic disease prevention and control strategies. Methods A prospective cohort study was conducted among adults aged 18–79 years in Beijing. A face-to-face questionnaire, along with body measurements and laboratory tests, were administered to 42,548 participants. Follow-up data on CVD hospitalizations and mortality through December 31, 2022, were collected using the Beijing Hospital Discharge Information System and the Beijing Death Registry Reporting Information System. Data were age- and/or gender-standardized based on the 2020 Beijing census population. Poisson regression models were employed to analyze the adjusted rates. The Fine-Gray competing risks model was used to calculate cumulative recurrence rates. Results Between 2012 and 2022, the crude and standardized incidence rates of CVD were 723.1 and 816.9 per 100,000 person-years, with an annual growth rate of 5.5% (95% CI: 4.1, 7.0) and 1.5% (95% CI: -1.1, 4.1), respectively. The standardized incidence rates of ischemic heart disease (IHD) and stroke were 507.7 and 436.2 per 100,000 person-years, with an annual change rate of 0.5 (95%CI: -2.1, 3.2) and 3.9% (95%CI: -0.3, 8.4), respectively. After adjusting for age, gender and living areas, the adjusted incidence rates for stroke increased annually among males, those aged 18–59, non-diabetic patients, obese individuals, and those with one chronic disease, increased annually. The crude and standardized mortality rates of CVD were 73.2 and 137.5 per 100,000 person-years, with annual changes of 13.0% (95% CI: 8.0, 18.2) and 8.0% (95% CI: -1.8, 18.7), respectively. The 10-year cumulative recurrence rates for CVD were 52.8%. Conclusion From 2012 to 2022, the crude incidence rate of CVD showed a long-term upward trend, the standardized incidence rate remained relatively stable, and predominantly driven by IHD, with a high cumulative recurrence rate. The rising incidence of stroke among males, those aged 18 to 59, non-diabetic patients, obese individuals, and those with one chronic disease, should be reversed.